Cube orientation bands observed in largely deformed Al-Sc alloys containing shearable precipitates. (June 2019) - Dan, C.Y.; Chen, Z.; Ji, G.; Zhong, S.Y.; Li, J.; Li, X.R.; Brisset, F.; Sun, G.A.; Wang, H.W.; Ji, V.
Abstract: Al-0.2 wt% Sc alloys, with uniformly dispersed nano-precipitates, were cold-rolled to determine the effects of precipitates on the development of Cube orientation texture during deformation. The macrotexture and microtexture of deformed alloys were characterized by Neutron diffraction and high-resolution electron backscattered diffraction, respectively. Residual Cube orientation components in the form of narrow bands were observed in the deformed alloys containing shearable precipitates, but absent in alloys without precipitates. This retention of Cube orientation bands was discussed to be the result of texture development retardation in alloys containing shearable precipitates, as precipitates were sheared by dislocations and inhibit the cross-slip. Graphical abstract: Unlabelled Image